The influence of occupational licensing and regulation - Morris M. Kleiner (IZA World of Labor, 2017)
Since the end of World War II, occupational licensing has been one of the fastest growing labor market institutions in the developed world. The economics literature suggests that licensing can influence wage determination, the speed at which workers find employment, pension and health benefits, and prices. Moreover, there is little evidence to show that licensing improves service quality, health, or safety in developed nations. So, why is occupational licensing is growing when there are such well-established costs to the public?
Keywords: J44; 330; occupational licensing; labor markets with regulation; wage determination with regulation